Protecting Newborns from Pertussis. Issue 1 (January 2017) - Wisner, Kirsten
Abstract : Pertussis in newborns is associated with severe morbidity and mortality. Perinatal nurses can play an important role by encouraging pregnant women to get the vaccine at designated intervals recommended by the Centers for Disease Control and Prevention and American College of Obstetricians and Gynecologists.